Introduction to parallel computing. - Grama, Ananth, ....-; Gupta, Anshul, ....-; Karypis, George, ....- (Harlow : Pearson, 2003)
Introduction to Parallel Computing is a complete end-to-end source of information on almost all aspects of parallel computing from introduction to architectures to programming paradigms to algorithms to programming standards. It is the only book to have complete coverage of traditional Computer Science algorithms (sorting, graph and matrix algorithms), scientific computing algorithms (FFT, sparse matrix computations, N-body methods), and data intensive algorithms (search, dynamic programming, data-mining).